A developmental study of eye movements in Hebrew word reading: the effects of word familiarity, word length, and reading proficiency - Lahoud, Hend; Share, David L.; Shechter, Adi (Frontiers in Psychology, 2023)
Previous studies examining the link between visual word recognition and eye movements have shown that eye movements reflect the time-course of cognitive processes involved in reading. Whereas most studies have been undertaken in Western European languages written in the Roman alphabet, the present developmental study investigates a non-European language ‒ Hebrew, which is written in a non-alphabetic (abjadic) script. We compared the eye-movements of children in Grades 4 to 6 (N = 30) and university students (N = 30) reading familiar real words and unfamiliar (pseudo)words of 3 letters and 5 letters in length. Using linear mixed models, we focused on the effects of word familiarity, word length, and age group. Our results highlighted both universal aspects of word reading (developmental and familiarity (lexicality) effects) as well as language-specific effects (as in the case of word length) which appear to be related to the uniquely morphological and orthographic features of the Semitic abjad.